2021
DOI: 10.1371/journal.pone.0249231
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for in-hospital mortality in laboratory-confirmed COVID-19 patients in the Netherlands: A competing risk survival analysis

Abstract: Background To date, survival data on risk factors for COVID-19 mortality in western Europe is limited, and none of the published survival studies have used a competing risk approach. This study aims to identify risk factors for in-hospital mortality in COVID-19 patients in the Netherlands, considering recovery as a competing risk. Methods In this observational multicenter cohort study we included adults with PCR-confirmed SARS-CoV-2 infection that were admitted to one of five hospitals in the Netherlands (Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
13
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
7
13
2
Order By: Relevance
“…On the other hand, a Turkish study revealed that the MEWS score calculated in the emergency room effectively predicted death in the forthcoming 28 days in patients with COVID-19 who required hospitalization [ 26 ]. The results of this study were in line with findings from a large cohort of 1000 patients from five Dutch hospitals [ 45 ]. A retrospective analysis of data from Wuhan showed that the MEWS was accurate in predicting in-hospital mortality in elderly patients with SARS-CoV-2 infection [ 46 ].…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, a Turkish study revealed that the MEWS score calculated in the emergency room effectively predicted death in the forthcoming 28 days in patients with COVID-19 who required hospitalization [ 26 ]. The results of this study were in line with findings from a large cohort of 1000 patients from five Dutch hospitals [ 45 ]. A retrospective analysis of data from Wuhan showed that the MEWS was accurate in predicting in-hospital mortality in elderly patients with SARS-CoV-2 infection [ 46 ].…”
Section: Discussionsupporting
confidence: 90%
“…Most studies published to-date have focused on mortality or severe COVID-19, although the findings were similar to those in the current study [36,37,38] [40].…”
Section: Discussionsupporting
confidence: 87%
“…ACE (angiotensinconverting enzyme) inhibitors, diuretics, and β-blockers were more frequently used in no survivors than in survivors. Nijman et al [14] in the Netherlands found no increased mortality risk in male patients, or patients with high BMI or diabetes. In the systematic review developed by Flook et al [15], age was a prominent predicting factor for death in hospitalized patients with SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 90%